System Failure: Work Organization and Injury Outcomes among Latino Forest Workers. Issue 2 (3rd April 2019) - Wilmsen, Carl; Castro, A. Butch de; Bush, Diane; Harrington, Marcy J.
ABSTRACT: Objectives : Forestry services is a hazardous industry with high job-related injury, illness, and fatality rates. The Northwest workforce is largely Spanish-speaking, Latino, and immigrant, working in poor conditions with insufficient attention paid to safety and health. Institutional racism fundamentally shapes the structural vulnerability of Latino immigrant workers. Given this context, we sought to understand how workplace organizational factors and safety climate affect job-related injuries in this industry. Methods : We developed 23 case studies from personal interviews after selecting from an initial participant survey pool of 99 Latino forest workers in southern Oregon who had been injured at work in the previous 2 years. Workers were recruited through snowball sampling and door-to-door canvassing. Questions spanned work conditions, tasks, employer safety practices, injury experience, medical treatment, and workers' compensation benefits. Results : Workers reported broken bones, chainsaw lacerations, back pain, heat and pesticide illnesses, and other occupational injuries. One-third of the cases fell into a Systems Functional category in which they reported their injuries to their supervisors and received medical treatment and workers' compensation benefits. The remaining two-thirds experienced System Failures with difficulties in receiving medical treatment and/or workers' compensation benefits, employer direction to not report, being fired, or seeking alternative home remedies. Conclusion : Workers employed by companies with more indicators of safety climate were more likely to obtain adequate treatment for their injuries and fully recover. Workers for whom interpretation at medical exams was provided by someone unaffiliated with their employers also reported better treatment and recovery outcomes.